The development and assessment of a scale to measure the experience of an anorexic voice in anorexia nervosa - Hampshire, K; Tierney, S; Varese, F; Haddock, G; Saeidi, S; Fox, JRE (Wiley, 2020)
The anorexic voice (AV) is defined as a critical internal dialogue, which has been implicated in the development and maintenance of anorexia nervosa (AN). Systematic research to explore this further requires a valid and reliable measurement tool. This study aimed to develop and assess the validity of the Experience of an Anorexic VoicE Questionnaire (EAVE‐Q). EAVE‐Q items were developed and checked for face and content validity through cognitive interviews with seven individuals diagnosed with AN. Participants with a diagnosis of AN (N = 148) completed the EAVE‐Q, sociodemographic questions and measures of mood and quality of life to assess internal consistency and construct validity. Forty‐nine participants completed the EAVE‐Q twice more to assess test–retest reliability. The EAVE‐Q had good face and content validity and good acceptability. Principal axis factoring resulted in an 18‐item scale organized into five domains with high internal consistency (α = 0.70 to α = 0.85). Domains correlated significantly with eating disorder symptoms, psychological distress, and quality of life. The EAVE‐Q did not discriminate between participants on the basis of body mass index. Test–retest reliability was moderate. Although the factor structure of the EAVE‐Q requires replication in other AN samples, the EAVE‐Q is the first measure of a critical internal dialogue in AN. It is hoped that it will aid future research to increase understanding of AN and the continued development of person‐centred treatments.